1997
DOI: 10.1046/j.1365-2141.1997.d01-2053.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics adds independent prognostic information in adults with acute lymphoblastic leukaemia on MRC trial UKALL XA

Abstract: Summary. Cytogenetic classification of 350 adults with acute lymphoblastic leukaemia on MRC UKALL XA trial showed the following statistically significant associations: t(9;22) (11%) increased with increasing age and leucocyte counts (WBC) and most had a C/pre-B immunophenotype. t(4;11) (3%) was associated with higher WBCs, increasing age and null immunophenotype. Other abnormalities of 11q (abn11q) (4%) were associated with male sex and T-cell ALL. High hyperdiploidy (7%) and abn9p (5%) decreased with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
143
1
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(163 citation statements)
references
References 17 publications
16
143
1
3
Order By: Relevance
“…20,21 Recently, TEL/AML1 translocation was identified in childhood ALL and was deemed relevant to prognosis. 22,23 TEL/AML1 translocation is exclusively expressed in ALL patients between 1 and 5 years of age and decreases with age.…”
Section: Figurementioning
confidence: 99%
“…20,21 Recently, TEL/AML1 translocation was identified in childhood ALL and was deemed relevant to prognosis. 22,23 TEL/AML1 translocation is exclusively expressed in ALL patients between 1 and 5 years of age and decreases with age.…”
Section: Figurementioning
confidence: 99%
“…[28][29][30] In this study, only one case showed Philadelphia chromosome among seven karyotyped ALLm cases. Although the number of cases was limited, this result means ALLm is an independent morphologic variant not related to any cytogenetic aberrations.…”
Section: Discussionmentioning
confidence: 94%
“…1,2,4 BMT from a sibling donor is a more effective treatment with 2-year DFS probabilities of 38 and 46% for patients in 1st CR and 41 and 28% for patients beyond 1st CR in the IBMTR series 5 and the series reported by Chao et al 6 Radich et al 7 reported 30 patients who received BMT in CR or relapse, of whom nine were disease-free beyond 2 years. Casper et al 8 reported 68% DFS at 13 months in 14 paediatric patients who received BMT in CR.…”
mentioning
confidence: 97%